If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(4 + x) = 7 2x + (4 * -1 + x * -1) = 7 2x + (-4 + -1x) = 7 Reorder the terms: -4 + 2x + -1x = 7 Combine like terms: 2x + -1x = 1x -4 + 1x = 7 Solving -4 + 1x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 7 + 4 1x = 7 + 4 Combine like terms: 7 + 4 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| 2x+x+6x=153 | | 5-3x+2=8-3x | | 2x-4*(x-4)=2y | | 9m*(-3)= | | x^3-45x^2+10000=0 | | 4x+3-x=-6x-7 | | 7x(3+b)=28 | | 2e-6=0 | | 293X-1= | | 1/3x5/6x9/10 | | X-5=9+X | | 7g-11=24 | | (5.4/x)=(.5^6) | | 12+15y-y=12 | | (k^2)-5k-10=0 | | (k^2)-5k+10=0 | | (k^2)-5k-4=0 | | (k^2)-5k+4=0 | | (2-3i)*(x+yi)=5-i | | 4x=6-1 | | 2x+3x-2x= | | 4(m-2)-8+2m=6(m+5) | | Ax+4y+4x+ay= | | x=1.04*y+6.18 | | 2x+3y+1z=51.4 | | X^3/3=65 | | X/3=65 | | 6(y-5)=4(y+2) | | 5y=10x+2 | | x*2-8=8 | | 5n+4=2n+33 | | 3(a+7)=36 |